The Effectiveness of Islamic Religious Education in Shaping the Character of Elementary School Students - Niskaromah; Abdullah, Anna Christina; Amalia, Putri (Zabags International Journal of Education, 2025)
Islamic Religious Education (IRE) plays a strategic role in fostering students’ religious character from an early age, particularly at the elementary level, which serves as a crucial foundation for children’s moral and spiritual development. Amid the challenges of globalization and the declining influence of religious values within family environments, the effectiveness of IRE implementation in instilling Islamic values has become an essential issue for in-depth investigation. This study aims to evaluate the effectiveness of IRE in shaping the religious character of elementary school students and to identify the supporting and inhibiting factors influencing the process. Employing a descriptive qualitative approach with a phenomenological strategy, data were collected through interviews, observations, and documentation involving IRE teachers, students, school principals, and parents, and then analyzed thematically using triangulation techniques. The findings reveal that the effectiveness of IRE is strongly influenced by teachers’ exemplary behavior, the habituation of religious practices within the school environment, and family involvement, although challenges remain regarding instructional methods and the continuity of religious values outside the school setting. This study contributes to the development of a more integrative and contextual Islamic character education practice and offers direction for strengthening collaboration among schools, families, and communities in nurturing religiously devoted young generations from an early age.